2014
DOI: 10.1002/aenm.201301973
|View full text |Cite
|
Sign up to set email alerts
|

Integrating ZnO Microwires with Nanoscale Electrodes Using a Suspended PMMA Ribbon for Studying Reliable Electrical and Electromechanical Properties

Abstract: A simple method for making electrical connections to ZnO microwires is reported. By using a suspended poly(methyl methacrylate) (PMMA) ribbon, it is shown that it is possible to electrically contact 1-2 µm diameter ZnO microwires with metal electrodes that are only 90 nm thick. The contact resistances of ZnO microwire-based electronic devices fabricated by this method are lower than those of devices fabricated by standard electronbeam lithography and evaporation processes. As one of the possible device applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
1
10
1
Order By: Relevance
“…Then, the flakes were transferred to other substrates with different thicknesses of SiO 2 (2.9À302 nm) by the following steps. 41 Optical images were obtained using a Nikon eclipse LV150 with an optional optical filter. The intensity of the image was obtained using ImageJ software.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the flakes were transferred to other substrates with different thicknesses of SiO 2 (2.9À302 nm) by the following steps. 41 Optical images were obtained using a Nikon eclipse LV150 with an optional optical filter. The intensity of the image was obtained using ImageJ software.…”
Section: Methodsmentioning
confidence: 99%
“…The dynamic flexural measurements were carried out at room temperature and in a low vacuum condition of around 3 × 10 –3 Torr. The SiN beams were actuated by mechanical stimuli induced from the vibration of a piezo-ceramic located underneath the substrate . When the AC frequency applied to the piezo-ceramic matches the mechanical resonance frequency of the SiN beam, the beam exhibits resonance behavior.…”
Section: Methodsmentioning
confidence: 99%
“…The SiN beams were actuated by mechanical stimuli induced from the vibration of a piezo-ceramic located underneath the substrate. 13 When the AC frequency applied to the piezo-ceramic matches the mechanical resonance frequency of the SiN beam, the beam exhibits resonance behavior. An optical interferometry technique, suitable for detecting resonance behavior of insulating devices, was employed to detect the vibrational motion.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported on the integration of various micro- and nanostructures on micropatterned electrodes. Relevant examples are p-type field effect transistors using CuO nanowires (NWs) 2 , photoconductive-terahertz detectors with single GaAs NWs 3 , electromechanical devices with ZnO microwires (μ-wires) 9 , photodetectors based on SiC and ZnO NWs 10 11 .…”
mentioning
confidence: 99%